THE ROLE OF INFORMATION TECHNOLOGY IN EDUCATION THROUGH THE INTERNET WORLD - Melani Dewi Lusita (STMIK Jakarta, 2003)
The development of rapid information technology becomes a facilitator for information. TheInternet is one way to get information. With the Internet students can get the rightinformation to and as a means of interaction between students with different culturalbackground.